ICCREM 2016 : BIM Application and off-Site Construction : proceedings of the 2016 International Conference on Construction and Real Estate Management : September 29-October 1, 2016, Edmonton, Alberta, Canada - Wang, Yaowu; Al-Hussein, Mohamed; Shen, Qiping; Zhu, Yimin (College teacher) (American Society of Civil Engineers, 2017)
This collection contains 182 peer-reviewed papers on BIM and prefabricated technology for construction engineering presented at the 2016 International Conference on Construction and Real Estate Management, held in Edmonton, Alberta, Canada, September 29-October 1, 2016.